Health Promoting Lifestyle during Covid-19 Pandemic among Residents of Gandaki Province, Nepal - Shrestha, K.; Acharya, S.; Poudel, S. (Kathmandu University Medical Journal, 2022)
Background Lifestyle is an important factor to individual’s health and quality of life. Although, the emergence of Corona virus disease 2019 (COVID-19) has forced billions of people to change their lifestyle overnight. Objective To identify health promoting lifestyle during COVID-19 pandemic among the residents of Gandaki Province, Nepal. Method Descriptive cross sectional web based study was conducted among 386 respondents from Gandaki Province. Adults from 18 years and above, who could fill the form online were included using purposive and snowball sampling technique. Data were collected using Health Promoting Lifestyle Profile II (HPLP II) scale and analysed using descriptive (frequency, percentage, median) and inferential statistics (Mann Whitney U test and Kruskal Wallis test). Result Only 18.7% of the respondents had an excellent health promoting lifestyle followed by good health promoting lifestyle among 60.4%. Highest median score was observed in spiritual 27(10-36), and interpersonal relationship subscale 27(9-36). Whereas, the lowest was observed in physical activity 21(8-32) followed by stress management 24(10-32). Statistically significant difference was observed in age and perception of own health status with spirituality; gender, chronic illness and perception of own health status with interpersonal subscale and age, gender, marital status, occupation and perception of own health status with physical subscale. Conclusion The study concludes the need of health education and awareness to promote healthy lifestyle behaviours with a particular emphasis on indoor physical activities and stress management skills with specific consideration to female and elderly.